ISSUES OF INNOVATIVE APPROACHES AND APPLICATION OF INFORMATION TECHNOLOGIES IN THE METHODOLOGY OF TEACHING FOREIGN LANGUAGES. - Toshkenbayeva Mushtariy (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, the process and methods of education through foreign language, the science of teaching a foreign language, the method of studying the activity of the teacher and the student, including the methodology of teaching a foreign language, and the types of modern methods used in it and their use it is mentioned.